(untitled) (Biological Sciences - PJSIR, 2007)
Rhynchophorus phe onicis larval oil was extracted, and characterized by physical and chemical methods. The lipid content of the larva was 25.30 ± 0.20% (wet weight) . The oil was golden-yellow, odourless and fluid at room temperature (26 ± 2 °C). Lipid analysis revealed that the larval oil comprised of 88.40 ± 0.35% neutral lipid, 8.20 ± 0.1 1 % phospholipid and 2.60 ± 0.10% glycolipids. The unsaturated fatty acids accounted for 61 . 10 % of the total fatty acids whereas, the saturated fatty acids constituted 38.90% of the fatty acids. Further analysis revealed refractive i ndex of 1 .30 ± 0.05, specific gravity of 0.89 ± 0.0 I , solidification val ue of 12-14 °C, total lipid phosphorus of 31.00 ± 0.25 (µg/g l i pid), acid value of 3.50 ± 0.06, iodine value of 123.60 ± 0.24, saponification val ue of 198.90 ± 0.25, and unsaponifiable matter of 8.60 ± 0.1 8. These values when compared with that observed in oils which have been consid ered to be of high q uality, and of much use in the pharmaceutical i ndustries , suggested that R . ph eonicis larval oil may have pharmaceutical potential.